2000
DOI: 10.1096/fasebj.14.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Dual specificity phosphatases: a gene family for control of MAP kinase function

Abstract: Mitogen-activated protein (MAP) kinases are important players in signal transduction pathways activated by a range of stimuli and mediate a number of physiological and pathological changes in cell function. MAP kinase activation requires phosphorylation on a threonine and tyrosine residue located within the activation loop of kinase subdomain VIII. This process is reversible even in the continued presence of activating stimuli, indicating that protein phosphatases provide an important mechanism for MAP kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
702
2
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 740 publications
(715 citation statements)
references
References 87 publications
8
702
2
3
Order By: Relevance
“…In addition, we found that Cdc25A was a phosphatase both for phospho-ERK-2 and for phospho-EGFR (Vogt et al, 2001;. Several other p-ERK phosphatases have more recently been described and reviewed (Camps et al, 2000).…”
Section: Cellular Consequences Of K Vitamin Interaction With Ptpsmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, we found that Cdc25A was a phosphatase both for phospho-ERK-2 and for phospho-EGFR (Vogt et al, 2001;. Several other p-ERK phosphatases have more recently been described and reviewed (Camps et al, 2000).…”
Section: Cellular Consequences Of K Vitamin Interaction With Ptpsmentioning
confidence: 65%
“…This class of PTP is important, as its members are overexpressed in tumors (Galaktionov et al, 1995b;Cangi et al, 2000;Hernandez et al, 2001), are involved in cell cycle control of Cdks (Camps et al, 2000), and are transcriptional targets of c-myc (Galaktionov et al, 1996). Inhibitors of PTPases represent a new approach to interference with the cell cycle and also a novel set of tools for dissecting the role of phosphatases in specific cellular signaling pathways.…”
Section: Future Directionsmentioning
confidence: 99%
“…It has been shown that reactive oxygen species promotes the activation of MAPK proteins by inhibiting MAP kinase phosphatases [55]. These phosphatases can dephosphorylate both phosphorylated threonine and phosphorylated tyrosine (dual specificity) residues and inactivate MAPK signaling [56]. It has been shown that MKP-1 (a family of dual-specificity protein phosphatases) can inactivate all three major MAPKs, including ERK, JNK and p38 [57].…”
Section: Discussionmentioning
confidence: 99%
“…This rapid phosphorylation and dephosphorylation of ERK occurs prior to the induction of MKP expression and may thereby also involve other classes of protein phosphatases that can influence the ERK cascade (Camps et al, 2000). First, the protein serine/ threonine phosphatase, PP2A can dephosphorylate the phosphothreonine residue of MAP kinase.…”
Section: Discussionmentioning
confidence: 99%